Eating Behavior of patients with Type 2 Diabetes and/or Hypertension: Eating behavior of patients with Diabetes and Hypertension - Farias Martins-Filho, Antonio Orlando; dos Santos Leal, Caroline; de Araújo Eymael, Diana; Kilpp, Débora Simone; Rota Borges, Lúcia; y Castro Marques, Anne; Pandolfo Feoli, Ana Maria; Torres Abib Bertacco, Renata (Journal of Health Care, 2024)
Introduction: Obesity, diabetes mellitus, and systemic arterial hypertension constitute the main chronic non-communicable diseases associated with inadequate nutrition. To help patients achieve lifestyle changes, an important step is to identify behavioral profiles. Aims: This study aimed to characterize the eating behavior of Brazilian adult patients with diabetes and hypertension and compare its domain scores between sex, age groups, and body mass index (BMI). Methods: The cross-sectional study assessed eating behavior domains in patients from the Diabetes and Hypertension Center of the Federal University of Pelotas using the Three-Factor Eating Questionnaire. It also compared behavioral patterns between different groups. Results: A total of 97 volunteer patients were included, with the majority being elderly (60.82%) and female (61.86%). Cognitive Restraint had the highest score among the domains. Females scored higher in Emotional Eating (EE) than males (p<0.003). Adults had significantly higher scores in EE (p<0.001) and Uncontrolled Eating (UE) (p<0.010) domains compared to the elderly. Subjects with overweight scored high in EE (p=0.003) and UE (p=0.028) across the sample. Adults with overweight had a higher EE score (p=0.014), while adults with obesity had higher scores for both EE (p=0.036) and UE domains (p=0.041). Conclusion: Differences in domain scores based on sex, age group, and BMI were observed. Understanding the eating behavior of this population can be crucial for planning effective interventions to address diabetes and hypertension management.